PENENTUAN FAKTOR PRIORITAS MAHASISWA DALAM MEMILIH TELEPON SELULER MERK BLACKBERRY DENGAN FUZZY AHP - Shega, Hanien Nia H; Rahmawati, Rita; Yasin, Hasbi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2012)
This study aims to determine the priority factor Diponegoro University students in choosing a BlackBerry mobile phone brands. Consumer or buyer is often confused in making the decision to buy a product because of the many factors that affect the choices available. From the method of Analytic Hierarchy Process (AHP) was found to be too subjective assessment of uncertainty for qualitative data. The problems above can be solved by the method of Fuzzy Analytic Hierarchy Process (FAHP), which uses the interval so that the assessment of qualitative data can provide a more objective assessment. The criteria used to be in this research are quality, price, design, and service. The data were taken by spreading questionnaires. From the answer of respondent, calculation of ratio was performed with a consistency ratio (CR). If CR<0.10 it means the answer of respondent is consisten and can be used for Fuzzy AHP. Based on the result of research, it could be concluded that quality was the top priority with 0.278 priority weights, then the service with 0.254 priority weights, design with 0.240 priority weight, and price with 0.228 priority weights.